Selection and mode effects in risk preference elicitation experiments - Hans-Martin von Gaudecker; Arthur van Soest; Erik Wengström (Institute for the Study of Labor (IZA), 2008)
We combine data from a risk preference elicitation experiment conducted on a representative sample via the Internet with laboratory data on students for the same experiment to investigate effects of implementation mode and of subject pool selection. We find that the frequency of errors in the lab experiment is drastically below that of the representative sample in the Internet experiment, and average risk aversion is also lower. Considering the student-like subsample of the Internet subjects and comparing a traditional lab design with an Internet-like design in the lab gives two ways to decompose these differences into differences due to subject pool selection and differences due to implementation mode. Both lead to the conclusion that the differences are due to selection and not implementation mode. An analysis of the various steps leading to participation or non-participation in the Internet survey leads shows that these processes are selective in selecting subjects who make fewer errors, but do not lead to biased conclusions on risk preferences. These findings point at the usefulness of the Internet survey as an alternative to a student pool in the laboratory if the ambition is to use the experiments to draw inference on a broad population.
Keywords: C90; 330; Risk aversion; internet surveys; laboratory experiments; Risikoaversion; Studierende; Befragung; Test; Niederlande